Does corruption contribute to the rise of the shadow economy? Empirical evidence from Uganda - Stephen Esaku (Cogent Economics & Finance, 2021)
This paper investigates whether corruption has contributed to the rise of the shadow economy in Uganda. Using autoregressive distributed lag bounds testing approach and granger causality econometric methods we find a positive relationship between corruption and the size of the shadow economy in both the long- and short-run. Additionally, the causality results reveal a bidirectional causal relationship between the shadow economy and corruption, and vice versa. These findings suggest that, for the case of Uganda, an increase in corruption contributes to the rise in the size of the shadow economy and vice versa, all else equal. Given the complementary relationship between corruption and the size of the shadow economy, addressing widespread informality in the country would require; first, reforming the political system to tackle political corruption and go after politicians who use their influence and power to circumvent institutions. Second, carrying out institutional reforms to address political patronage and influence peddling would go a long way into addressing systemic corruption which in turn could help mitigate the spread of informal sector activities. Third, strengthening the enforcement of existing laws to identify and punish culpable public officials who use their offices for private gain would also address the level of informality in the country.
Keywords: D73; H26; K49; O17; O5; 330; Corruption; country-level studies; informal sector; shadow economy; tax evasion and avoidance